Targeting Viral RNA-Dependent RNA Polymerases as an Antiviral Therapy - Miranda, Daniel; Sanchez, David J. (Current Medicinal Chemistry, 2021)
Progressive globalization of our society brings not only worldwide integration, it also increases and promotes our exposure to new viral pathogens with evident impacts on our global health. Especially with the emergence of SARS-CoV-2, our biomedical research infrastructure has never been more compelled to rapidly develop antiviral regimens that demonstrate improved efficacy against these pathogens. Here, we showcase 3 poignant antivirals against the lucrative target, RNA-dependent RNA polymerase (RdRP) of RNA viruses – a timely and relevant topic given the present efforts against COVID-19. While effective drug designs against RdRP are important, their benefit and potential as a standard of care truly relies on them standing out in well-designed clinical trials.
Keywords: ribavirin